Trail in the redwoods with a boarded walk and railing - Unknown:::Creator::::::::::::
Photograph shows a trail in the redwoods. Part of the trail is a boarded walk with a railing. It is probably located at the YWCA's Camp Ayun Mapu in Big Basin.